The effect of exercise function - investigating an alternative explanation for ''runner's high'' - Wohlwend, M.; Olsen, A.; Haberg, A.; Palmer, H. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
The exercise induced transient hypofrontality theory (eTHT) has been proposed as an alternative neurophysiological explanation for the mood and cognition enhancing effect of aerobic exercise (1), popularly known as "the runner's high".In light of the computational demands of movement, eTHT hypothesises that hypoactivity occurs, particularly in the prefrontal cortex during exercise. The prefrontal cortex is involved in executive function (2). Connor's Continuous Performance Test (CCPT) was used to investigate changes in attention and executive control during and post treadmill running exercise in young healthy volunteers (n=30, 15 male, 15 female). Subjects performed a VO2max test to assess aerobic capacity and maximum heart rate (MHR). In separate sessions, for which the order was randomised subjects performed CCPTs at rest and during low intensity (LI; 63% MHR) and moderate intensity (MI; 75% MHR) treadmill running exercise. In a second phase of the study subjects performed isocalorifically matched exercise bouts, in separate sessions in a randomised order, of LI, MI and high intensity interval training (HIT). The HIT session consisted of 4x4 intervals: 4x4 min 90% MHR with 3 min recovery at 60- 70% MHR. For the statistical analysis repeated measure ANOVAs were done for both the during exercise and the post exercise tests. Preliminary statistical analyses of the CCPT results gave the following results. Values are means ± S.E.M., compared by ANOVA. Choice reaction time (HitRT) increased significantly during exercise (LI 323.2 ± 34.1 ms; MI 324.1 ± 34.4 ms) compared to at rest (309.1 ± 39.4 ms; p.0.005). Commission errors were not significantly different during exercise, compared to at rest but showed a trend to increase during exercise compared to baseline (p=0.08). The findings for the post exercise CCPTs showed that choice reaction time (HitRT) decreased significantly from rest (309.1 ± 39.4 ms) to post exercise levels (LI 282 ± 36 ms; MI 276.6 ± 33.95 ms; HI 275 ± 30.9 ms) in an exercise intensity dependent, linear fashion (p.0.0001). Commission errors were not significantly different post exercise, compared to at rest but showed a linear increasing trend with intensity (p=0.075). The main preliminary findings of the current study are that volunteers made the same level of commission errors during exercise and at rest, regardless of exercise intensity. The lack of change in impulsive errors during exercise paired with increasing reaction times during running may imply reduced activity in the prefrontal cortex during exercise, consistent with eTHT. According to the post exercise CCPT results HitRT was decreased post exercise compared to rest, with a linear trend for exercise intensity (p.0.0001). This may imply prefrontal cortex hyperactivity post exercise and thus has implications for elite performance in a variety of sports.